Patient Satisfaction After Stella Maris Hospital and Faisal Islamic Hospital Were Installed in Makassar City: An Examination of the Role of Brand Perception, Customer Perceived Value, and Customer Experience - Zakiyah Ramdlani Hamzah; Noer Bahry Noor; M. Alimin Maidin; Fridawaty Rivai; Lalu Muhammad Saleh; Nasruddin Nasruddin (PSPP JOURNALS, 2022)
Patient satisfaction at inpatient installations at Stella Maris Hospital and Faisal Islam Hospital in Makassar City will be analyzed and compared with respect to brand image, customer perceived value, and customer experience. The research in question is a quantitative cross-sectional study that employs an observational methodology. A total of 190 replies were included in this study, all of which were from patients being treated at either RS Stella Maris or RS Islam Faisal Makassar. Bivariate and multivariate univariate analysis were used to examine the data. Based on the data collected, it was determined that there was a link between patient happiness and brand equity, customer value perception, and customer service quality. Brand image had a significance level of 0.0000.05, and its value was 0.126. Value as seen by customers had a 0.0000.05 significance level, and nilai equaled 0.424. We found a value of B = 0.376 for customer satisfaction at a significance level of 0.0000.05. Management at both RS Stella Maris and RSI Faisal Makassar City would do well to regularly assess the hospitals' brand values, customer perceptions of those values, and the quality of care their patients receive, with suggestions for ways to enhance these metrics including faster service, clearer communication, and more accommodating scheduling.